2008
DOI: 10.1097/jcp.0b013e31816777f7
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of α-Lipoic Acid Treatment of Antipsychotic Drug-Induced Weight Gain in Patients With Schizophrenia

Abstract: Weight gain and other metabolic disturbances have now become discouraging, major side effects of atypical antipsychotic drugs (AAPDs). The novel strategies required to counteract these serious consequences, however, should avoid modulating the activities of the neurotransmitter receptors involved because those receptors are the therapeutic targets of AAPDs. Adenosine monophosphate-activated protein kinase is an enzyme that plays a pivotal role in energy homeostasis. We hypothesized that alpha-lipoic acid (ALA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 56 publications
5
33
0
Order By: Relevance
“…There is a large body of growing evidence showing that LA can have a substantial role in the regulation of food intake and anthropometric indices by suppressing appetite and elevating energy metabolism. 8,9,11,12 In agreement with our study there are two human studies; in a randomized, double-blind, placebo-controlled, 20-week trial, 1800 mg LA reduced body weight significantly more than did 1200 mg LA and placebo in 360 obese individuals. 10 In a case series study by Kim et al, 9 the effect of LA on body weight gain induced by antipsychotics in schizophrenic patients was studied (N = 7, 1200 mg LA, 12 weeks).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…There is a large body of growing evidence showing that LA can have a substantial role in the regulation of food intake and anthropometric indices by suppressing appetite and elevating energy metabolism. 8,9,11,12 In agreement with our study there are two human studies; in a randomized, double-blind, placebo-controlled, 20-week trial, 1800 mg LA reduced body weight significantly more than did 1200 mg LA and placebo in 360 obese individuals. 10 In a case series study by Kim et al, 9 the effect of LA on body weight gain induced by antipsychotics in schizophrenic patients was studied (N = 7, 1200 mg LA, 12 weeks).…”
Section: Discussionsupporting
confidence: 75%
“…7 In addition, ALA reduces body weight and changes other anthropometric indices by suppressing appetite and increasing metabolism. [8][9][10][11][12] Spinal cord injury (SCI) is a devastating condition and entails considerable burden on the individual and society. 13,14 Persons with chronic SCI are at increased risk for obesity, cardiovascular disease, hypertension, diabetes, dyslipidemia and systemic inflammation [15][16][17][18][19] because of changes in their lifestyle, body composition and fat mass.…”
mentioning
confidence: 99%
“…schizophrenia (Kim et al, 2008, Ratliff et al, 2013. The medications metformin, dfenfluramine, sibutramine, topiramate, and reboxetine were also confirmed in a recent metaanalysis to attenuate antipsychotic-related weight gain (Maayan et al, 2010).…”
Section: Accepted M Manuscriptmentioning
confidence: 78%
“…Potentially, suffering from both conditions may increase neuroprogressive pathways and lead to worsening treatment outcomes, relapse or treatment resistance. Adjunct interventions that may be considered include the addition of anti-inflammatory drugs such as COX-2 inhibitors (Muller and Schwarz, 2008) and the TNF antagonist, infliximab (Raison et al, 2013), medications with neuroprotective properties (e.g., antidepressants, mood stabilisers) (Dodd et al, 2013, Malhi et al, 2012, herbs and nutrients with anti-inflammatory and antioxidant properties (e.g., curcumin, resveratrol, omega-3 fatty acids, green tea, n-acetyl cysteine, CoQ10, selenium, zinc, alpha lipoic acid and vitamins such as A, C and E) (Alappat and Awad, 2010, Floyd, 1999, Kim et al, 2008, Lopresti et al, 2012, Scapagnini et al, 2012 and lifestyle changes known to enhance neurogenesis (e.g., sleep hygiene interventions, meditation, yoga, relaxation therapies and exercise) (Doraiswamy and Xiong, 2007, Kiecolt-Glaser et al, 2010, Lopresti et al, 2013.…”
Section: Do Obese and Overweight Psychiatric Populations Require Specmentioning
confidence: 99%
“…ALA reduces body weight and changes other anthropometric indices through increasing metabolism and suppressing appetite (9)(10)(11)(12)(13). However, beside these, it is indicated that with no change in energy intake, ALA could protect the liver against fat accumulation as well as hypercholesterolemia (14,15).…”
Section: Introductionmentioning
confidence: 98%